Administration of Native Courts and Enforcement of Native Customary Laws in Sarawak - Lang, Empeni (Journal of Malaysian and Comparative Law, 2019)
The Native Courts are purely a creature of statute, viz the Native Courts Ordinance (Cap. 43): Their jurisdiction is clearly defined by the the legislature and the powers of the courts are strictly limited... The Native Courts including the District Native Court are statutory courts established not by the Federal law but by Sarawak State law. They administer a system of laws entirely different from that of the High Court and the Subordinate Courts in Sarawak.